Reflections on the concept of musical development. Issue 1 (March 2022) - Welch, Graham F.
Abstract: 'The Sequence of Musical Development' by Swanwick and Tillman was published in the British Journal of Music Education (BJME) in 1986. This year marks its 35 th anniversary and provides an occasion to look back on the article's content and legacy. It is also an opportunity to reflect on the antecedents for the article's underlying concepts, as well as how our understanding of children and young people's musical behaviours and development has evolved. Alternate and more nuanced perspectives, both available at the time and since, draw on an expanding, diverse, multidisciplinary research base. These enable us to have a better grasp of the strengths of the original, as well as what continues to need investigation.